Marked By Belief: The Dark Superstition Of Child Branding (Indian Internet Journal of Forensic Medicine and Toxicology, 2025)
Branding often referred to by local tribal communities as ‘asaeba,’ ‘chapba,’ ‘lachba’  or ‘chenka is the process of inflicting burns on the skin of a living being. The act of  branding in children, particularly as part of a superstitious belief, is harmful and  unethical. It is essential to emphasize that branding or marking children can have  severe physical and psychological consequences. Such actions are generally not  supported by ethical or legal standards and can lead to serious harm to the child’s  well-being. Two distinct cases were brought to the Pediatric Trauma and Emergency  Department at the tertiary care center of Raipur: one involving a history of loss of  consciousness, and the other presenting with seizures, both accompanied by multiple  burn wounds over the body. Clinical forensic medicine unit consultation was sought  in view of the unusual presentation of burn wounds, which upon detailed evaluation  was found to be branding, a superstitious practice in villages with an intention to  cure the disease. The act of branding as part of a superstitious belief is a culturally specific practice  that can vary widely across societies and communities. It is crucial to approach these  topics with cultural sensitivity and understanding of human rights and child welfare.  A differential diagnosis of child abuse should be considered when dealing with such  cases.
Keywords: Branding in children; Superstition; Child abuse; Therapeutic burns